An integrated optimization - simulation model for water allocation in an irrigation project - Mohanty, Binayak Prasad; Mizutani, Masakazu; Bogardi, Janos J.; Murty, V.V.N.; Singh, Gajendra; Paudyal, Guna N.; Government of Australia (Bangkok : Asian Institute of Technology, 1987)
An explicit stochastic dynamic programming model is used in this study to derive the optimum operation policies of the single-purpose Kanjhari reservoir, in India, that minimizes the expected annual squared deviation between target irrigation demand and reservoir release, satisfying the system constraining conditions. The model used the backward-looking stochastic dynamic programming algorithm with reservoir inflows treated as the first order Markov chain. The optimal monthly operation policies are expressed in terms of final storage state at the end of each month, as the function of the initial storage state at the beginning of the current month, and the inflow during the current month. Achieving the optimal release policy by stochastic reservoir operation model, the optimal al location policy between the main canals, and the feasible crop acreage of different competing crops in the command area were estimated by the simulation model using a physical performance indicator with an objective to, minimize the accumulated deviation function from the "most ideal" configuration of the system for 35 consecutive crop years of historical record. The simulation model was tried with different parameters and criteria. A reliability analysis was also carried out to investigate the rela tive performance of the system at different system configuration, which can serve as a tool to decision estimator, or project planner for the optimal irrigation project planning and operation. Due to the physical basis of optimization, this combined model is well suitable for any single purpose irrigation project within the limited data requirement.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1987
Keywords: Water in agriculture -- Mathematical models